2015
DOI: 10.1016/j.vaccine.2015.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Promoting influenza vaccination: Insights from a qualitative meta-analysis of 14 years of influenza-related communications research by U.S. Centers for Disease Control and Prevention (CDC)

Abstract: Introduction A primary mission of the U.S. Centers for Disease Control and Prevention's (CDC) is promoting immunization against seasonal influenza. As with most education efforts, CDCs influenza-related communications are often informed by formative research. Methods A qualitative meta-analysis of 29 unpublished, primarily qualitative CDC-sponsored studies related to flu and flu vaccination knowledge, attitudes and beliefs (KABs). The studies, undertaken between 2000 and 2013, involved focus groups, in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
116
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 23 publications
11
116
0
Order By: Relevance
“…HCPs’ knowledge of influenza vaccine has been directly correlated with vaccination uptake [10, 11]. In a meta-analysis of studies sponsored by the US Centers for Disease Control and Prevention, HCPs’ misconceptions about influenza vaccination were similar to those held by the general public [12]. Similarly, in a study by Gesser-Edelsburg et al concerning Israeli HCP's attitudes towards the avian influenza vaccine in an outbreak setting, there was no difference between HCP and the general public regarding support for vaccination [13].…”
Section: Discussionmentioning
confidence: 99%
“…HCPs’ knowledge of influenza vaccine has been directly correlated with vaccination uptake [10, 11]. In a meta-analysis of studies sponsored by the US Centers for Disease Control and Prevention, HCPs’ misconceptions about influenza vaccination were similar to those held by the general public [12]. Similarly, in a study by Gesser-Edelsburg et al concerning Israeli HCP's attitudes towards the avian influenza vaccine in an outbreak setting, there was no difference between HCP and the general public regarding support for vaccination [13].…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative meta-analysis of 14 years of influenza-related communications research by the CDC, public and some health care provider perceptions and beliefs were difficult and slow to change. 83 A study by Freed et al 84 reported that 11.5% of parents of adolescents refused immunization. The meningococcal vaccine was declined 31.8% of the time and the HPV vaccine was declined 56.4% of the time.…”
Section: Understanding Barriers To Immunizationmentioning
confidence: 99%
“…To inactivate non-specific inhibitors, sera were treated with receptor destroying enzyme prior to being tested. [24][25][26][27][28] The HI titers were determined in assays by the reciprocal dilution of the last well that contained non-agglutinated red blood cells and were conducted in duplicate. Positive and negative serum controls were included for each plate.…”
Section: Hemagglutination Inhibition Assaymentioning
confidence: 99%